New Equation for Estimating Outdoor Thermal Comfort in Humid-Tropical Environment. - Sangkertadi, S; Syafriny, R (European Journal of Sustainable Development, 2014)
This paper presents the results of research focusing on thermal comfort at outdoor spaces in humid tropical climate. The study was conducted in the city of Manado, Indonesia in the years 2011 and 2012, by way of field-experimentation and measurements of microclimate. From the results of measurements and questionnaires, it was carried out development of regression equations. Through statistical analysis it has been generated three thermal comfort equations for outdoor, which each for normal walking, brisk walking, and sitting with doing a moderate activity. Equations are functions of Ta(air temperature), Tg(globe temperature), v(wind velocity), RH(Relative humidity) and Adu(body surface area). The output of the equations is scale of thermal comfort level referring to PMV (Predicted Mean Vote), where 0 is comfortable or neutral, +3 is very hot, -2 is cold, .etc. The equations are uniquely for the people wearing tropical clothing type (about 0.5 to 0.7 clo). The validation of the equations was done through comparison with other equations that originated from the studies of non-tropical humid climates. Simulations using the equations were also be done in order to know effect of micro climate on outdoor thermal comfort. Keywords: thermal comfort, tropical-humid, micro-climate, Manado